PUTUSAN MAHKAMAH KONSTITUSI TENTANG PEMILU SERENTAK DIHUBUNGKAN DENGAN PENCEGAHAN KORUPSI POLITIK - Dedi Mulyadi; M. Rendi Aridhayandi (Universitas Suryakancana, 2015)
Given the importance of the elections in a democracy, the principle of keeping the elections in accordance Luber Jurdil, especially of political corruption. Then on January 23, 2014 the Constitutional Court passed a decision in a judicial review of Law No. 42 of 2008 on General Election of President and Vice President of the Constitution of the Republic of Indonesia Year 1945, by decision No. 14 / PUU-XI /2013 decided elections simultaneously at in 2019 and beyond. Concurrent elections is one of the prevention of political corruption. Political corruption is an act of power holders in order to take advantage of the power. For example: the financing of political parties, the purchase